Colonization and population dynamics of total, viable, and culturable cells of two biological control strains applied to apricot, peach, and grapevine crops - Daranas, Núria; Badosa, Esther; Montesinos, Emilio; Bonaterra, Anna (Frontiers in Microbiology, 2024)
The ecological fitness of the biological control strains Bacillus velezensis A17 and Lactiplantibacillus plantarum PM411 was evaluated in different crops, geographical zones, and growing seasons. Both strains (2 g L -1 of dried formulation) were spray inoculated on apricot and peach trees, and grapevines. Depending on crop, flowers, fruits, and leaves were picked at several sampling time points. The population dynamics of viable, viable but non-culturable, and dead cells were studied by comparing viability qPCR (v-qPCR), qPCR, and plate counting estimations. A17 showed high survival rates in apricot, peach, and grapevine organs. The A17 viability was confirmed since qPCR and v-qPCR estimations did not significantly differ and were rather constant after field applications. However, higher population levels were estimated by plate counting due to the non-selective characteristics of the medium used. The viability of PM411 was constrained by plant organ, crop, and climate conditions, being higher in apricot than in grapevine. PM411 survival declined after field application, indicating difficulties in its establishment. The PM411 population level was made up of dead, culturable, and viable but non-culturable cells since significant differences between the three methods were observed. In conclusion, A17 and PM411 differ strongly in their survival in grapevine, peach, and apricot.